Lessons learned from 9/11: Mental health perspectives on the COVID-19 pandemic. (June 2020) - DePierro, Jonathan; Lowe, Sandra; Katz, Craig
Abstract: The COVID-19 pandemic will likely lead to high rates of PTSD, depression, and substance misuse among survivors, victims' families, medical workers, and other essential personnel. The mental health response to the 9/11/01 terrorist attacks, culminating in a federally-funded health program, provides a template for how providers may serve affected individuals. Drawing on the 9/11 experience, we highlight effective prevention measures, likely short and long-term treatment needs, vulnerable subgroups, and important points of divergence between 9/11 and the COVID-19 pandemic. Mental health monitoring, early identification of at-risk individuals, and treatment irrespective of financial barriers are essential for minimizing chronic distress.